TABOO AND EUPHEMISM IN UZBEK AND TAJIK LANGUAGES - Surayya SAMIYEVA (Scholar Express Journal, 2023)
The article is devoted to the study of taboos and euphemisms in the Uzbek and Tajik languages. In this article, euphemism is compared with another linguistic-cultural sign - taboo. Particular attention is paid to the identification of similarities and differences in the activities of the respective units of the Uzbek and Tajik languages. The article shows that one of the main functions of euphemism is to replace the names of forbidden things, and also analyzes psychological motives, because in the linguistic literature, euphemism issues are considered, as a rule, in connection with the taboo phenomenon. This may be related to the specificity of the linguistic phenomenon. The article examines the problem of using social euphemisms in modern Uzbek and Tajik languages
Keywords: Euphemism; dysphemism; taboo